Civil society. local, regional or transnational?: Some reflections from Latin America (2014)
This essay aims to examine the possibilities for developing a regional civil society in the Latin American context. By analyzing the process of democratization on the continent as well as some academic discussions about the concept of civil society, several successful experiences in terms of accountability and citizen mobilization are examined. Although itrecognizes the appearance of new forms of organization and action from civil society with a sizeable regional impact, conclusions are that discredit of the democratic system and the incapacity of the economic model to overcome exclusion and social inequality constitute the main ob stacles for its realization.